Sustainable Tourism Education in Lerep Village, Semarang Regency - Rialini Retno Alyssa Cahyani; Eva Banowati; Ananto Aji; Hariyanto Hariyanto; Erni Suharini (Universitas Negeri Semarang, 2025)
This study aims to analyze sustainable tourism education in Lerep Tourism Village, Semarang Regency, by examining four key components: the forms of educational tourism offered, and the implementation of sustainable tourism principles. Using a mixed-methods approach, quantitative data were collected through questionnaires to assess tourist attraction potential and the effectiveness of educational programs, while qualitative data were obtained through in-depth interviews, observation, and documentation to evaluate Pokdarwis readiness and sustainability practices. The results show that Pokdarwis demonstrates good readiness in fulfilling its roles as facilitator, educator, representative, and technical operator, although improvements are still needed in technical skills and environmental management. The village possesses strong natural, cultural, and man-made attractions that support the development of educational tourism, including environmental education, cultural learning, and community-based training activities. Sustainable tourism principles have been applied, particularly in environmental conservation, community involvement, and local economic empowerment, yet some aspects require further optimization. The study concludes that Lerep Tourism Village has significant potential to strengthen sustainable tourism through structured educational programs, enhanced community capacity, and integrated management led by Pokdarwis.